If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -1)(n + -5) = 0 Reorder the terms: (-1 + n)(n + -5) = 0 Reorder the terms: (-1 + n)(-5 + n) = 0 Multiply (-1 + n) * (-5 + n) (-1(-5 + n) + n(-5 + n)) = 0 ((-5 * -1 + n * -1) + n(-5 + n)) = 0 ((5 + -1n) + n(-5 + n)) = 0 (5 + -1n + (-5 * n + n * n)) = 0 (5 + -1n + (-5n + n2)) = 0 Combine like terms: -1n + -5n = -6n (5 + -6n + n2) = 0 Solving 5 + -6n + n2 = 0 Solving for variable 'n'. Factor a trinomial. (1 + -1n)(5 + -1n) = 0Subproblem 1
Set the factor '(1 + -1n)' equal to zero and attempt to solve: Simplifying 1 + -1n = 0 Solving 1 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1n = 0 + -1 -1n = 0 + -1 Combine like terms: 0 + -1 = -1 -1n = -1 Divide each side by '-1'. n = 1 Simplifying n = 1Subproblem 2
Set the factor '(5 + -1n)' equal to zero and attempt to solve: Simplifying 5 + -1n = 0 Solving 5 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1n = 0 + -5 -1n = 0 + -5 Combine like terms: 0 + -5 = -5 -1n = -5 Divide each side by '-1'. n = 5 Simplifying n = 5Solution
n = {1, 5}
| 2u(u-4)=0 | | 2(7x-8)+5=14x-11 | | (16-8)3+22/11= | | (5d-7)(7d+2)=0 | | d+12=20-3d | | x-4.3=23 | | p(p+7)=0 | | -24s+-53=39+-s | | (t-8)(t-5)=0 | | 7x+6-3x=13x+17 | | x-4.3=19 | | -1-2=3y | | -54=-4(3n+1)+2n | | (7v+3)(7v+9)=0 | | y=-2x^5+16x^4+66x^3 | | z^2-5z+7+z=0 | | 15z^2+7z-16=0 | | g(9g+7)=0 | | 8x+8=38 | | x+8.8=33 | | .80x+.85(40)=.40(75) | | (f-8)(8f-5)=0 | | 7x+3-2x+9-5x=19 | | (1+2i)(1-2i)=0 | | 2.25=-2.67x-1.83x | | 8a+11=3a+41 | | x+7.7=33 | | (r-8)(r+1)=0 | | x-25=-65 | | 6(r-4)=-5r+31 | | y=10x^4-360x^2 | | (k-8)(k+2)=0 |